Zad.1
a)3/7-(2,5*7/25-0,2)=
b)2+(2+(2+(2+2))-2)-2=
c)0,12*3/4-(3/5-2,1*5/7)=
d)((3,2+7/8):2,5-0,62)*(-100/3)=
e)4*(0,6-3/5:(-3))=
f)((2 1/3-1 3/4)+5/12):(-0,02-0,08)=
g)(-1/9+1 1/6):(1/6-1 1/3)=
h)1,44:2 2/5-(0,75-1 1/3)*(-4/5)=

Zad.2
a)3 3/4*1 1/5+(-1,5):2,4-1/4=

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-02T17:37:08+01:00
3/7-(2,5*7/25-0,2)= -0,0714285714285714
2+(2+(2+(2+2))-2)-2=6
0,12*3/4-(3/5-2,1*5/7)=0,99
((3,2+7/8):2,5-0,62)*(-100/3)= -33,6666666666667
4*(0,6-3/5:(-3))=3,2
((2 1/3-1 3/4)+5/12):(-0,02-0,08)= -41,6666666666667
(-1/9+1 1/6):(1/6-1 1/3)= -0,492063492063492
1,44:2 2/5-(0,75-1 1/3)*(-4/5)= -2,32024242424242



3 3/4*1 1/5+(-1,5):2,4-1/4=17,275